Porous ceramic cups for soil solution extiaction - Moraes, José Francisco Valente; Dynia, José Flávio (Pesquisa Agropecuaria Brasileira, 2014)
Sou selution samples of a well drained latosol (LE-oxisol) and of a lowland flooded soU (Low-}lumic Gley - LHG) were collected with porous ceramic cups and analysed weekly. The pomos ceramic cups were kept iii the soU during the whole sampimg periods (15 weeks for the Lii soil and 22 weeks for the LIIG soil). The movement of Ca, Mg, K and NOT ipi the LE soU profile and the iiicrease in Fe in the solution of the LUO soU were observed. Obstruction of the ceramie cups pores by a progressive deposition of coiloidal material on the external surface of tbe cups and precipitation of Fe oxi-hydroxides on the internal surface of the cups were problems one observed that reduced the efficiency of the ceramic eups in laking reliable soi.l solution samples